2017
DOI: 10.1021/acscentsci.7b00419
|View full text |Cite
|
Sign up to set email alerts
|

Combating Drug-Resistant Mutants of Anaplastic Lymphoma Kinase with Potent and Selective Type-I1/2 Inhibitors by Stabilizing Unique DFG-Shifted Loop Conformation

Abstract: Targeted inhibition of anaplastic lymphoma kinase (ALK) dramatically improved therapeutic outcomes in the treatment of ALK-positive cancers, but unfortunately patients invariably progressed due to acquired resistance mutations in ALK. Currently available drugs are all type-I inhibitors bound to the ATP-binding pocket and are most likely to be resistant in patients harboring genetic mutations surrounding the ATP pocket. To overcome drug resistance, we rationally designed a novel kind of “bridge” inhibitor, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 44 publications
0
41
0
Order By: Relevance
“…In fact, our data support that ceritinib can inhibit the efflux of ABCB1-mediated the conventional chemotherapeutic drugs to enhance the accumulation of these drugs in MDR leukemia cells, and to restore the sensitivity of ABCB1-overexpressing MDR cells to these conventional chemotherapeutic drugs, while having weak effect on their parental cells. Additionally, although ceritinib has been shown excellent antiproliferation activity in different ALK-positive cancer cells by inhibiting ALK phosphorylation and subsequent downstream survival signaling of ALK, such as ERK, p-ERK, AKT and p-AKT [41], some studies also have shown that activation of ERK or PI3K/AKT pathway is attributable to the resistance to conventional chemotherapeutic drugs in various cancer cells [42, 43]. In our study, we found that ceritinib could reverse ABCB1-mediated MDR and enhance the efficacy of conventional chemotherapeutic drugs at more than 85% cell survival concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, our data support that ceritinib can inhibit the efflux of ABCB1-mediated the conventional chemotherapeutic drugs to enhance the accumulation of these drugs in MDR leukemia cells, and to restore the sensitivity of ABCB1-overexpressing MDR cells to these conventional chemotherapeutic drugs, while having weak effect on their parental cells. Additionally, although ceritinib has been shown excellent antiproliferation activity in different ALK-positive cancer cells by inhibiting ALK phosphorylation and subsequent downstream survival signaling of ALK, such as ERK, p-ERK, AKT and p-AKT [41], some studies also have shown that activation of ERK or PI3K/AKT pathway is attributable to the resistance to conventional chemotherapeutic drugs in various cancer cells [42, 43]. In our study, we found that ceritinib could reverse ABCB1-mediated MDR and enhance the efficacy of conventional chemotherapeutic drugs at more than 85% cell survival concentration.…”
Section: Discussionmentioning
confidence: 99%
“…To address the infection of pathogenic bacteria, antibiotics are inevitably and excessively utilized in clinical disinfection therapies. However, up to now, the adaptive tendency of pathogens on drug resistance produces a great threat to current therapeutic systems in combating diverse bacterial infections . Hence, novel and efficient antibacterial materials and strategies are urgently needed to reduce the dependence on antibiotic treatments .…”
Section: Introductionmentioning
confidence: 99%
“…The binding free energy (∆ G bind ) for each system was calculated by the Molecular Mechanics/Generalized Born Surface Area (MM/GBSA) methodology in AMBER according to the Equation :(Chen et al., , ; Genheden & Ryde, ; Gohlke, Kiel, & Case, ; Hou, Li, & Wang, ; Hou, Wang, Li, & Wang, ,; Hou, Zhu, Chen, & Xu, ; Liu, Yao, Wang, & Han, ; Pan et al., ; Sun, Li, Li, & Hou, ; Sun et al., ; Sun, Li, Shen, et al., ; Sun, Li, Tian, et al., ; Xu, Li, Li, Zhou, & Hou, ; Xu, Sun, Li, Wang, & Hou, ; Xue et al., ; Xue, Qi, et al., ; Xue, Wang, et al., ; Yang, Shen, Liu, & Yao, ; Yang et al., ; Zhang, Hou, Wang, & Liu, ) ΔGnormalbind=Gnormalcomplex+GnormalproteinGnormalligand=ΔH+ΔGnormalsolvationTΔS=ΔEnormalMM+ΔGnormalGB+ΔGnormalSATΔSwhere ∆ E MM is the gas‐phase interaction energy between protein and ligand, consisting of electrostatic (∆ E ele ) and VDW interactions (∆ E vdw ). The polar and non‐polar contributions of the solvation free energy represented by ∆ G GB and ∆ G SA .…”
Section: Methodsmentioning
confidence: 99%